PENGARUH KUALITAS PRODUK DAN KUALITAS LAYANANAN TERHADAP PEMBELIAN ULANG PELANGGAN PT CARITA SARI PRATAMA - Kartini Dwi Ambarwati; Amanda Setiorini (Jurnal Manajemen Bisnis Krisnadwipayana, 2020)
This study aims to determine the effect of product quality and service quality on merchandise repurchases at PT Carita Sari Pratama using quantitative descriptive research. The analytical method used is simple linear regression analysis. The results showed that the product quality and service quality simultaneously and partially had a positive and unidirectional relationship. Meanwhile, the results of the calculation of the correlation coefficient and determination show that there is a very close relationship between the variable product quality and service quality on purchases at PT Carita Sari Pratama.